Complementary and Alternative Medicine Use by Breast Cancer Patients at Time of Surgery Which Increases the Potential for Excessive Bleeding. (March 2015) - Andersen, M. Robyn; Sweet, Erin; Zhou, May; Standish, Leanna J.
Objective . The use of complementary or alternative medicine has increased greatly over the last decade. This study describes a cross-sectional survey of women with breast cancer to describe their use of herbs and supplements that might have placed them at elevated risk for bleeding at the time of their primary treatment surgery for breast cancer. Methods . We present cross-sectional survey results from a cohort of 316 women with breast cancer. The participants included a convenience sample of 98 women who received integrative oncology treatment from local providers and a larger group of women recruited from the local cancer registry who were matched on their similarity to the integrative oncology patients' demographic characteristics and stage of cancer at time of diagnosis. Results . Almost 16% of women with breast cancer report using one or more herbs or supplements thought to potentially increase their risk for adverse bleeding-related outcomes at the time of their primary surgical treatment. This does not include the 22% who used fish and flaxseed oils, which were at one time thought to increase risk for bleeding but for which there is now evidence to suggest that they are safe. Conclusion . Further research is needed to better understand the risks associated with use of a variety of herbs and supplements among women approaching surgery.